Tetranychus urticae (Koch, 1836) em cultivo de lúpulo Humulus lupulus L. (Cannabaceae) no Rio Grande do Sul, Brasil - primeiro relato de ocorrência - Wurlitzer, Wesley B.; Johann, Liana; Ferla, Noeli J.; Silva, Guilherme L. (Entomological Communications, 2021)
Tetranychus urticae Koch (Koch, 1836) is considered one of the main pests in hop crops Humulus lupulus L. (Cannabaceae) when found in high densities, as it causes leaf browning, plant defoliation and attack on flowers, reducing productivity and quality of the plant production. In this sense, the present study aims to record for the first time the occurrence of T. urticae and its injury to hops in Rio Grande do Sul State. The injuries observed were irregular spots, web formation and leaf browning. It was also observed Phytoseiulus macropilis (Banks, 1904) preying on T. urticae.